Carlos Ramos: The poetics of a legal historian. Notes on his contributions to the discipline of law and literature - Coaguila Valdivia, Jaime Francisco (2022)
The work of Carlos Ramos Núñez is characterized by having intertwined history, law and literature, therefore, his contributions to the discipline of Law & Literature from his drive for the dissemination of these studies through the Peruvian Journal of Law and Literature and the publication of the emblematic book “The quill and the law. Lawyers and judges in the Peruvian narrative” (2007) must be revisited to understand the origin of the vocation of the legal historian within his family constellation; as well as the merit of his academic and human contributions in the consolidation of the happy couple: law and literature.